2021
DOI: 10.1007/s00228-021-03205-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed crises following benzodiazepine withdrawal: deficient adaptive mechanisms or simple pharmacokinetics? Detoxification assisted by serum-benzodiazepine elimination tracking

Abstract: Objective Rapid relapses after successful withdrawal occur even in apparently motivated benzodiazepine (BZD)-dependent patients. Regardless of known personality or biological (re-adaptation) issues, the aim of this open-label, single-arm, seminaturalistic study was to search for any detoxification errors contributing to failures. Methods The data came from 350 inpatients. Based on serum-BZD evolution criteria, the procedure was divided into four stages: su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The detoxification procedure included 4 stages [ 5 ]. Substitution Following popular approaches, the detoxification was preceded by replacing the formerly used BZDs with a standard long-acting BZD.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detoxification procedure included 4 stages [ 5 ]. Substitution Following popular approaches, the detoxification was preceded by replacing the formerly used BZDs with a standard long-acting BZD.…”
Section: Methodsmentioning
confidence: 99%
“…To date, these delayed/protracted crises have been attributed to individual inertia of biological readaptation processes. However, the first large-sample study using serum BZD concentration tracking revealed that the timing of the last of consecutive withdrawal crises, which was often (45%) the strongest one, was correlated with the time at which the concentration reached zero [ 5 ]. These results are in line with both older small-sample studies on BZDs [ 6 8 ] and modern views on discontinuing medications at all [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations